"I'm haunted by it:" experiences of licensed counselors who had a client die by suicide. Issue 2 (3rd July 2021) - Jorgensen, Maribeth F.; Bender, Sara; McCutchen, Ashley
ABSTRACT: The purpose of this phenomenological study was to explore how licensed professional counselors (LPCs) experienced a client death by suicide. Data was collected through interviews with seven LPCs. The following four themes emerged: (1) elements that influenced grief; (2) impact on identities; (3) messages from self and others; and (4) healing strategies. The authors provide suggestions for clinicians, agencies, clinical supervisors, and training programs regarding pre-and-postvention support and advocacy.